Zestings de categorías modulares construidas a partir de grupos cuánticos de tipo A (2020)
This work aims to continue with the work started in the Article Braided Zesting and its Applications, the original and main result of this work is the classification of the braided zestings of fusion categories obtained from quantum groups of type A, that is, quantum groups obtained from the Lie algebra sl_N. The first chapter presents all the basic definitions, on fusion categories, necessary for this development, starting with the concept of a monoidal category until defining a modular category. Later, the concept of graduation by a finite group G of a fusion category is presented. In the second chapter, the concept of zesting is developed, which is a technique to obtain a new braided fusion category from a known braided fusion category. First, we introduce the basic definitions of zesting and then the main results on the characterization and classification of possible zestings on a cyclic group for a braided...